Educational intervention in the knowledge about hand hygiene in nursing students - André Luiz Thomaz de Souza; Fábio Bene; Heitor Ribeiro; Juliano de Souza Caliari; Deise Aparecida Carminatte; Angelita Maria Stabile (Universidad de Alicante, 2019)
Objective: To evaluate the effect of an educational intervention on knowledge about hand hygiene in nursing students. Method: Quasi-experimental study of the pre- and post-intervention type, carried out with 23 nursing students. Knowledge about hand hygiene was evaluated using a form containing questions about the subject. In addition, a theoretical and practical educational intervention was carried out with an average duration of 60 minutes each. Results: The results of the pre -and postintervention comparison revealed a significant increase in the number of correct answers, with emphasis on improved knowledge related to the question: What care should be taken with the hands, nails and with the use of ornaments? Conclusions: The educational intervention performed in this study proved to be efficient in improving knowledge about hand hygiene.